Pengaruh Work Environment, Career Development dan System Reward terhadap Pengembangan Sumber Daya Manusia Melalui Job Satisfaction sebagai Variabel Mediasi di Dinas Kesehatan Kota Tegal - Widiya Nurul Azmia; Slamet Bambang Riono; Nur Afridah; Muhammad Syaifulloh; Nur Khojin (Lembaga Pengembangan Kinerja Dosen, 2026)
The low effectiveness of the work environment, limited career development, and suboptimal reward systems have impacted employee job satisfaction and hindered the development of apparatus competencies. This study aims to analyze the influence of the work environment, career development, and reward systems on human resource development, with job satisfaction as a mediating variable among employees of the Health Office of Tegal City. The research employed a quantitative approach with data collected through questionnaires distributed to 120 respondents selected using purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) to test the relationships among variables. The findings indicate that career development has a significant effect on job satisfaction and also directly influences human resource development. However, career development mediated by job satisfaction does not significantly affect human resource development. Conversely, the reward system significantly influences human resource development through job satisfaction but does not have a significant direct effect. The work environment does not significantly affect job satisfaction but directly influences human resource development. Job satisfaction shows a positive but insignificant influence on human resource development. Overall, the results highlight that human resource capacity development is more strongly driven by a supportive work environment and clear career development programs, while the reward system plays an important role when it effectively enhances job satisfaction.